Locutionary, Illocutionary and Perlocutionary Acts in Films Gara-Gara Warisan - Femia Sarahdilla Raswati; Intan Sari Ramdhani (CV. Rayyan Dwi Bharata, 2023)
This research is motivated by the problem of using locutionary and perlocutionary speech acts in films because of inheritance. The purpose of this study is to describe the use of locutionary, illocutionary, and perlocutionary speech acts in the film Gara-gara Warisan. This study uses a qualitative method that is objective. The research technique used is the technique of literature review and data collection by the researchers themselves as key instruments. The results of this study found as many as 8 speech acts locutionary, illocutionary, perlocutionary.